The The Effects of Zumba Exercise on LDL Levels and Oxidative Stress of Young Adult Women - Putri, Alda Aulia Rahma Ananto; Supatmo, Yuswo; Setiawati, Erna; Ambarwati, Endang (RSUP Dr. Kariadi, 2021)
ABSTRACT Background: Sedentary lifestyle which refers to physical inactivity is one of the risk factors for non-communicable diseases, one of which is dyslipidemia. Zumba, as a form of aerobic exercise, is in great demand by young adults recently. This exercise has effects on reducing LDL levels and oxidative stress measured by malondialdehyde (MDA) levels as the biomarker. Objectives: To examine the effect of Zumba exercise on LDL and MDA levels in young adult women. Methods: This experimental study used two groups pre and post test design. Research subjects were 36 women, divided into intervention group (n=18) and control group (n=18). Zumba exercise was done by intervention group 2 times a week (60 minutes per session) for 8 weeks virtually. LDL and MDA levels were measured using blood samples of research subjects. Result data was analysed using T-paired test, Wilcoxon test and Mann-Whitney test. Results: There is no decrease in LDL levels from intervention group after 8 weeks of Zumba exercise. However, there is significant decrease in MDA levels. LDL levels increased from 94,18±25,60 mg/dL to 105,82±27,64 mg/dL (p<0,05) and MDA levels decreased from ,71±0,28 µmol/L to 0,37±0,64 µmol/L (p<0,05). There is no meaningful difference in LDL levels between intervention and control group. Nonetheless, there is meaningful difference in MDA levels among both groups. Conclusion: Zumba exercise 2 times a week for 8 weeks virtually can not reduce LDL levels but can significantly reduce MDA levels. Keywords: low density lipoprotein, malondialdehyde, Zumba exercise